2017
DOI: 10.2169/internalmedicine.8344-16
|View full text |Cite
|
Sign up to set email alerts
|

Congestive Heart Failure During Osimertinib Treatment for Epidermal Growth Factor Receptor (EGFR)-mutant Non-small Cell Lung Cancer (NSCLC)

Abstract: We herein report a case of congestive heart failure which developed during osimertinib treatment. A 78-year-old woman presented with mild exertional dyspnea three weeks after starting osimertinib for the treatment of epidermal growth factor receptor (EGFR) T790M-positive non-small cell lung cancer. She was diagnosed with congestive heart failure caused by the osimertinib. In contrast to trastuzumab, a human epidermal growth factor receptor 2 (HER2) monoclonal antibody that often causes cardiac dysfunction, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Recently, high dose osimertinib (160mg, once daily) showed survival benefit and tolerable safety profile in EGFR T790M positive NSCLC patients with central nervous system (CNS) metastasis who progressed on prior EGFR TKI [34]. However, a case of congestive heart failure caused by osimertinib, possibly due to the HER2 inhibition, was reported [35]. Furthermore, rate of QT prolongation, cardiac failure, CFC and A.fib were higher in osimertinib group compared to other TKIs and ECG monitoring for QT prolongation and monitoring for symptoms of heart failure should be considered while using osimertinib [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, high dose osimertinib (160mg, once daily) showed survival benefit and tolerable safety profile in EGFR T790M positive NSCLC patients with central nervous system (CNS) metastasis who progressed on prior EGFR TKI [34]. However, a case of congestive heart failure caused by osimertinib, possibly due to the HER2 inhibition, was reported [35]. Furthermore, rate of QT prolongation, cardiac failure, CFC and A.fib were higher in osimertinib group compared to other TKIs and ECG monitoring for QT prolongation and monitoring for symptoms of heart failure should be considered while using osimertinib [36].…”
Section: Discussionmentioning
confidence: 99%
“…Osi also has an inhibitory action on HER2 (ErbB2), 9 a subfamily of EGFR, suggesting the possibility that it causes left ventricular dysfunction by the same mechanism as Trastuzumab. 10 In addition, since the case report of the onset of cardiac failure due to the use of Osi have been reported in recent years, 11 we believe that it is necessary to evaluate cardiac function by echocardiography as appropriate. In our study, we found that although the LVEF decreased more than 10% from the baseline value, it did not reach <50%, and thus Osi was not withdrawn.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to respiratory adverse reactions, a very small number of patients seem to have developed cardiac adverse drug reactions to Osimertinib (Table 2). Watanabe et al and Oyakawa et al described two females, aged 78 and 84, respectively, who developed symptoms of congestive heart failure and dilated cardiomyopathy with no other obvious cause during their course of treatment with Osimertinib [10, 11]. One was 21 days and the other was 34 weeks into treatment [10, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al and Oyakawa et al described two females, aged 78 and 84, respectively, who developed symptoms of congestive heart failure and dilated cardiomyopathy with no other obvious cause during their course of treatment with Osimertinib [10, 11]. One was 21 days and the other was 34 weeks into treatment [10, 11]. These patients also improved with drug discontinuation and goal-directed medical therapy as well as diuretics.…”
Section: Discussionmentioning
confidence: 99%